2021
DOI: 10.1111/een.13027
|View full text |Cite
|
Sign up to set email alerts
|

Geographical, temporal and taxonomic biases in insect GBIF data on biodiversity and extinction

Abstract: 1. Analysis of geographic patterns of extinction must be accompanied by knowledge of biodiversity patterns. Such analysis is not yet available in insects given three shortfalls. First, knowledge of insect species' distribution is poor. Second, insect inventories have taxonomic, geographical, temporal and habitat biases. Third, the accelerated loss of insect species likely surpasses the rate at which the authors are discovering new species.2. The authors have examined the state of the art of knowledge of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 61 publications
2
47
0
1
Order By: Relevance
“…For example, longer-lived species may have greater lagged responses to global change drivers such as landuse change when compared with species with shorter generation times 13 . We found that birds were the best-, and arthropods the worst-represented taxa across the Living Planet, BioTIME and PREDICTS databases (Figure 5), as commonly found in ecological datasets 8,9,65 . Recently, invertebrates and in particular insects have been highlighted as a taxon experiencing potential steep declines in abundance and biomass 56,57 , yet such findings are confounded by the general paucity of invertebrate data [60][61][62] (but see 68 for a recent effort in compiling insect data).…”
Section: More and Less Well Represented Taxa May Respond Differently To Global Change Driversmentioning
confidence: 53%
See 2 more Smart Citations
“…For example, longer-lived species may have greater lagged responses to global change drivers such as landuse change when compared with species with shorter generation times 13 . We found that birds were the best-, and arthropods the worst-represented taxa across the Living Planet, BioTIME and PREDICTS databases (Figure 5), as commonly found in ecological datasets 8,9,65 . Recently, invertebrates and in particular insects have been highlighted as a taxon experiencing potential steep declines in abundance and biomass 56,57 , yet such findings are confounded by the general paucity of invertebrate data [60][61][62] (but see 68 for a recent effort in compiling insect data).…”
Section: More and Less Well Represented Taxa May Respond Differently To Global Change Driversmentioning
confidence: 53%
“…Taxonomic representation in biodiversity analyses could influence the detected global change responses, with certain taxa being more or less sensitive to global change [64][65][66][67] . For example, longer-lived species may have greater lagged responses to global change drivers such as landuse change when compared with species with shorter generation times 13 .…”
Section: More and Less Well Represented Taxa May Respond Differently To Global Change Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing the current crisis related to the loss of biodiversity necessarily involves addressing several fundamental knowledge gaps 1,2 . Currently there are vast spatial, temporal and especially taxonomic gaps and biases in global primary biodiversity data sets, and these biases are limiting our understanding of the earth's biosphere [3][4][5][6] . Automatic or semi-automatic observation methods based on image recognition hold great promise in solving some of the taxonomic biases currently experienced 7 .…”
Section: Introductionmentioning
confidence: 99%
“…increase/decrease of species abundance or richness over time) (hereafter called status) (Dirzo et al ., 2014; Cardoso et al ., 2020; Albert et al ., 2021). Despite that, biodiversity studies towards conservation actions (hereafter called solutions), such as the selection of priority areas, design of protected areas, and ecosystems restoration, have increased recently (Watson et al ., 2014; Godet & Devictor, 2018; Maas et al ., 2019; Rocha‐Ortega et al ., 2021), some of them testing and proposing solutions to prevent insect loss (Samways et al ., 2020). Conservation studies assessing threats, status, and solutions are equally important to implement strategies preventing decline of insect biodiversity.…”
Section: Introductionmentioning
confidence: 99%